Genetic, linguistic and archaeological perspectives on human diversity in Southeast Asia - Jin, Li; Seielstad, Mark; Xiao, Chunjie (Recent advances in human biology, 2001)
Southeast Asia is regarded as one of the birthplaces of modern humans. Recent genetic evidence shows that it was probably the entry point of modern humans from Africa into East Asia and Oceania. With the help of new markers X mostly from the Y-chromosome and mtDNA X several recent efforts have been made to study the populations of Southeast Asia, which have been somewhat neglected in the past. A new picture of the origin and migrations of modern humans in this region is quickly emerging. In this book, the leading researchers in the studies of Southeast Asian, East Asian, and Oceanian populations present the most up-to-date results of their research.